Pelatihan Sistem Informasi Pendataan Barang Berbasis Website di Biro Kepesantrenan Nurul Jadid - Ahmad Khairi; Serli Aliansyah; Siti Aisa; Eka Dewi Lestari (Transformative Service Journal, 2025)
The still-manual inventory management at the Nurul Jadid Islamic Boarding School Bureau has resulted in low bureaucratic efficiency and low transparency of the institution's assets. This situation demands digital transformation as a strategic step to support modern and accountable Islamic boarding school governance. This community service program aims to build staff independence in operating a website-based inventory information system to minimize data errors and expedite reporting. The implementation method uses a Participatory Action Research (PAR) approach involving 10 staff through stages of participatory preparation, technical training, and intensive mentoring. The results of the activity showed a significant increase in partner competency, marked by an increase in the average knowledge score from 73.3 (pre-test) to 95.3 (post-test). Based on skill observation indicators, participants proved capable of independently inputting data, updating stock, tracking item history, and printing inventory reports. A short-term impact seen during the mentoring was the creation of a valid initial database of the bureau's inventory. This success marks a shift in work culture from manual recording to a more organized digital system, resulting in more transparent and efficient management of Islamic boarding school assets.